DETERMINATION OF MINING ZONING ANDESITE, SIRTU AND TRAS MATERIALS IN PURBALINGGA DISTRICT CENTRAL JAVA - Ariyanto Ariyanto; Ahmad Fauzan Haryono; Dimas Chaidir Adinugroho (Physics Study Programme, Faculty of Science and Technology UIN Syarif Hidayatullah Jakarta, 2020)
Purbalingga Regency has quite a large amount of Andesite, Sirtu and Tras Digging Materials. So a research was carried out in Purbalingga Regency to assist the Ministry of Energy and Mineral Resources (ESDM) in Determining the Mining Permit Zoning. This research was conducted only in 5 districts, namely Karangrejo District, Bojongsari District, Bobotsari District, Mrebet District and Kutasari District.The potential of Andesite Excavation Material with 2,159,081,136BCM resources spread across Karangrejo District, Bojongsari District, Bobotsari District, Mrebet District, and Kutasari District. Sirtu with 14,859,100BCM resources scattered in Karangrejo District, Bobotsari District, Bojongsari District and Mrebet District. Meanwhile, Tras with 15,510,500BCM resources which are only scattered in Karangrejo District.The determination to get the permit is closely related to the 11 parameters that have been shown in map form. Each of these parameters has a rating, weight, and value and a ming process is carried out in order to determine whether the area is suitable for permits, eligible for conditional permits, and not worthy of permits. Scores 10-19.5 are directed to be granted permission, scores 20-29.5 are directed to be eligible for conditional permission, while ≥ 30 are directed to be not granted permission.The potential that is directed to be eligible for a permit is andesite 1,038,841,000BCM, Sirtu 6,861,400BCM and tras 9,280,500BCM, the potential that is directed to be eligible for conditional permits is andesite 67,520,000, sirtu 4,675,000BCM and tras 1,180,000BCM, while the potential that is directed is not feasible The permits are andesite 1,052,720.0BCM, sirtu 3,226,700BCM and tras 5,050,000BCM.